MiR-222 Overexpression May Contribute to Liver Fibrosis in Biliary Atresia by Targeting PPP2R2A. Issue 1 (January 2015) - Dong, Rui; Zheng, Yijie; Chen, Gong; Zhao, Rui; Zhou, Zhijian; Zheng, Shan
ABSTRACT Objective: Biliary atresia (BA) is a devastating liver disease in infants. Progressive hepatic fibrosis is often observed in postoperative patients with BA even after a successful Kasai portoenterostomy procedure. MicroRNA-222 (miRNA) has been linked to the activation of stellate cells and the progression of liver fibrosis. Methods: In this study, the miR-222 expression profile in BA and infants with anicteric choledochal cyst (CC) was determined. The functional effect of miR-222 inhibition on the growth of the human hepatic stellate cell line LX-2 was also evaluated. The downstream signaling pathways and target of miR-222 were determined by coupling gene expression profiling and pathway analysis and by in silico prediction, respectively. In addition, we demonstrated miR-222 overexpression in patients with BA compared with choledochal cyst controls. Results: Inhibition of miR-222 in the LX-2 cell line significantly decreased cell proliferation. We also identified protein phosphatase 2A subunit B as a target of miR-222. The downstream signaling pathway, Akt, was also influenced by miR-222. A consistent reduction of Akt phosphorylation and Ki67 in the LX-2 line was shown following miR-222 suppression. Conclusions: Our results show that miR-222 overexpression is common in BA and contributes to LX-2 cell proliferation by targeting protein phosphatase 2A subunit B and Akt signaling.